Apakah Jam Kerja Orang Tua dan Kondisi Sosial-Ekonomi Keluarga Berpengaruh Terhadap Kognitif Anak dalam Rumah Tangga Muslim di Indonesia? - Lintang Brilianti (Journal of Islamic Economics and Finance, 2025)
The purpose of this study is to identify the impact of parental working hours and family socio-economic conditions on children's cognitive development within Indonesian Muslim households. This research uses data from the Indonesia Family Life Survey (IFLS) waves 4 and 5, employing fixed effect regression methodology with Stata 15.1 software. The study sample includes children from Muslim households aged 7-14 years in IFLS 4 and the same individuals aged 14-22 years in IFLS 5. The findings indicate that father’s working hours have a significant positive effect on children's cognitive development. Higher income from longer working hours enables fathers to meet children's basic needs, such as education and healthcare, which contributes to improving their well-being and cognitive abilities. However, mothers' working hours do not significantly affect children's cognitive development. Socio-economic factors, such as children's education, also have a significant positive impact on their cognitive abilities, while children's employment status has a significant negative impact. Overall, longer fathers' working hours contribute to increased family income, which ultimately supports improved socio-economic conditions and children's cognitive development. This study provides new insights into the dynamics of Muslim families and policy recommendations to support family well-being and education based on Islamic values.